2010
DOI: 10.1590/s0100-40422010000400002
|View full text |Cite
|
Sign up to set email alerts
|

Selective hydrogenation of furfural on Ir/TiO2 catalysts

Abstract: Recebido em 23/1/09; aceito em 4/12/09; publicado na web em 8/4/10 Titania-supported Ir catalysts were used in the hydrogenation of furfural. Reactions were carried out in a stirred batch type reactor at 0.62MPa and 363K using a 0.10M solution of furfural in a 1:1 mixture n-heptane -ethanol as solvent. Catalysts containing 2 wt% of Ir were reduced in H 2 flow at different temperatures in the range 473-773K. The catalysts were characterized by H 2 chemisorption, TEM, TPR, TPD of NH 3 and XPS. Conversion of furf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
32
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(34 citation statements)
references
References 22 publications
2
32
0
Order By: Relevance
“…[5] The catalytic route to furfural through dehydration and isomerization today is still challenging route. [3] High selectivity to furfuryl alcohol (FA) has been demonstrated for numerous catalysts, [8][9][10][11][12][13][14][15][16][17] as the product of the first step in the hydrogenation pathway (Scheme 1b). [3] The hydrogenation route is a highly reported research area, as it can provide a wide range of bulk chemicals.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[5] The catalytic route to furfural through dehydration and isomerization today is still challenging route. [3] High selectivity to furfuryl alcohol (FA) has been demonstrated for numerous catalysts, [8][9][10][11][12][13][14][15][16][17] as the product of the first step in the hydrogenation pathway (Scheme 1b). [3] The hydrogenation route is a highly reported research area, as it can provide a wide range of bulk chemicals.…”
Section: Introductionmentioning
confidence: 99%
“…[3] High selectivity to furfuryl alcohol (FA) has been demonstrated for numerous catalysts, [8][9][10][11][12][13][14][15][16][17] as the product of the first step in the hydrogenation pathway (Scheme 1b). Supports often include Lewis acids, such as g-Al 2 O 3 , [14,21,22] TiO 2 , [12,16,23] ZrO 2 , [8] CeO 2 , [14] SiO 2 [9,10] and Al-SBA-15, [24] basic metal oxides (MgO and ZnO) [11,14] and base metal carbonates (CaCO 3 ), [10] which assist in polarizing the furfural carbonyl bond and which can actively take part in one of the reaction pathways. [12,18] The production of MF is attractive, as it has a very low boiling point which enables efficient separation.…”
Section: Introductionmentioning
confidence: 99%
“…In the profile obtained for Au-Ir/TiO 2 , it can be observed four peaks at about 375 K (a), 466 (b) and 570 K (g). Both α and b peaks could be assigned to the reduction of gold species 21 whereas, the g peak could be attributed to the reduction of IrO 2 species 21,[24][25][26] . The shift at higher temperatures of this peaks could be associated to a higher formation of surface oxychlorometal complex (MeO x Cl y where Me: Au or Ir) that inhibits the reduction of metal species 27 .…”
Section: Characterizationmentioning
confidence: 99%
“…This catalytic behavior, in which the main products are the unsaturated alcohols revealed that the catalyst surface possesses active sites with two types of metallic sites (Me° and Me δ+ ). It has been widely reported that if the active phase is present essentially as zero valent state, the favored reaction is the hydrogenation of the C=C bond in the α, β unsaturated aldehyde leading to saturated aldehyde, meanwhile, as the proportion of Me δ+ increases, the pathway shift to the reduction of the carbonyl bond due to this later species contributes to polarize the C=O bond making easier its hydrogenation [25][26][27] . Figure 3.…”
Section: Characterizationmentioning
confidence: 99%
“…In these studies, several thermal treatments were adopted as pre-processing steps before the hydro-chemical Ir dissolution to enhance its solubility. These steps are summarized here: [3][4][5][6][7][8][9][10][11][12][13][14] (1) alloying with base metals (Cu, Al, Ni, Pb), (2) fusion with alkali materials (Na 2 O 2 , NaOH), and (3) oxidation to IrO 2 by heating to 1100 C in oxygen. Even with these thermal treatment, the recovery rate is very slow.…”
Section: Introductionmentioning
confidence: 99%